Develop a mobile learning application on food labels - Tan, Chee Hong (Universiti Malaysia Sarawak (UNIMAS), 2015)
r:;he main purpose of this study is to develop a learning mobile application on food labels based on the instructional design plan proposed by Morrison Ross and Kemp. Mobile application is chosen as the learning tool for this study because the population of people owning a mobile device is increasing rapidly. Learning can be conducted anywhere and everywhere using a mobile device This mobile application shows learners the four basic steps in understanding food labels. More information are shown as well as quizzes at the end of the learning process. This learning application act as a very important tool for consumers when they are purchasing or consuming any food products. This is especially important for consumers with special diet such as patients with diabetes or high blood pressure. Keyword: learning, mobile application, food labels